Restoring Shoulder Function After AC Joint Dislocation: The Role of Adjustable Loop Fixation - Burli, Dr. Utkarsh; Manvi, Dr. Nikhil; Botta, Dr. Kavya; Udapudi, Dr. S.V.; Chanda, Dr. Amay (South Eastern European Journal of Public Health, 2025)
Acromioclavicular (AC) joint injuries, common in active young adults, differ significantly from glenohumeral joint injuries in structure, function, and clinical presentation. AC joint injuries primarily result from direct or indirect trauma. These injuries are classified using the Rockwood system, with high-grade separations often requiring surgical intervention. This study evaluates the effectiveness of AC joint fixation using an adjustable loop technique with Endo-button fixation performed at KLE Hospital and MRC, Belagavi. Inclusion criteria were patients aged 15-50 with AC joint dislocations, excluding those with associated shoulder pathologies or comorbidities. Post-operative improvement was assessed using the Nottingham Clavicle Score (NCS) and range of shoulder abduction. Results indicated significant improvement in shoulder function and abduction at 6 months post-surgery. The adjustable loop technique demonstrates a high success rate in restoring shoulder function, providing stable fixation and enabling progressive rehabilitation. While complications like clavicle prominence and the need for conversion to open surgery were observed in a few cases, the technique appears reliable for restoring shoulder function with minimal long-term deficits.